Introduction: Reading and Writing Berlin - Stephen Brockmann (Studies in 20th & 21st Century Literature, 2004)
On June 20, 1991, eight and a half months after the peaceful reunification of Germany, the German Bundestag voted 337 to 320 to move the capital of the Federal Republic from Bonn to Berlin…
Keywords: peaceful reunification of Germany; peace; reunification; Germany; Berlin; Bonn; Capital; Capital City; 1989; 1991; German Bundestag; Bundestag; Federal Republic